Students’ Preferences for Video Genres and Their Relationship to English Proficiency: Evidence from Indonesian University EFL Context - Prancisca, Stella; Rizqi, Muhammad Ainur; Aminullah, Fajar; Ningsih, Endah Setya (JOLLT Journal of Languages and Language Teaching, 2025)
This study investigates the relationship between English proficiency levels and video genre preferences in the Extensive Viewing (EV) program. The research aimed to understand how students’ language abilities influence their choice of video content, focusing on genres such as Folklore, Educational Video/Learning, Comedy, Drama Series, and General Knowledge/Science. The study involved 30 undergraduate students, and the data were collected through a post-program survey and viewing logs from the Canvas platform. A Chi-Square test was conducted to to determine the statistical significance of the relationship between genre preference and English proficiency. The results reveal that students with lower English proficiency tend to favor simpler genres, such as Comedy, which are easier to understand, while students with higher proficiency prefer more complex genres like Drama Series and General Knowledge/Science. The Chi-Square test confirmed a significant relationship between language proficiency and genre choice (p < 0.05). This suggests that video content should be selected based on studentsâ€™ language abilities to enhance comprehension and engagement. The study supports the theory of comprehensible input and differentiated instruction, highlighting the importance of tailoring materials to match students’ proficiency levels. The results have important implications for designing effective language learning programs, ensuring that the content is both accessible and challenging based on students’ individual needs. Further research with a larger sample and broader genre selection is recommended to deepen the understanding of students’ viewing preferences.